SP0035 Raynaud's phenomenon and systemic sclerosis: An update. (23rd January 2014) - Allanore, Y.
Abstract : Systemic sclerosis (SSc) is a multisystem auto-immune disease. The two main subtypes of SSc (limited and diffuse cutaneous subsets) typically have differing courses and prognoses. However, new classification criteria are under preparation and should allow to better identify SSc in the earliest stages, before skin involvement. In this line, there a renewed interest for Raynaud's phenomenon as an early symptom, and combined with anti-nuclear antibody or capillaroscopy testing, this may drive toward a window of opportunity for actively fighting against the progression of the disease. Recent work in SSc and related fibrotic diseases have identified several areas in which innate immunity can stimulate inflammation as well as fibrosis. This has been supported by several in vitro and in vivo data together with many genetic studies. Concomitantly, several lines of evidence have shown that epigenetic modifications contribute to the massive production of extracellular matrix proteins by skin fibroblasts. Proper categorization of SSc patients for research studies by use of new biomarkers potentially derived from these better understandings is critical, as disease heterogeneity may explain some of the inconsistencies of prior studies. Indeed, randomised controlled study mostly performed in patients with early diffuse cutaneous SSc have provided so far disappointing results. Some methodological limitations have been pointed out recently through meta-analysis and outcome measures need to be improved for assessing the fibrotic process. More consistent data have been reported for the vascular component of SSc with common vasodilators, such as calcium channel blockers and angiotensin converting enzyme inhibitors, and more potent drugs such as prostanoids, endothelin antagonists and phosphodiesterase V inhibitors. The most recent data obtained with these drugs will be presented and discussed together the preliminary experiences of the use of biologics in SSc. Disclosure of Interest: Y. Allanore Grant/Research support from: Actelion, Pfizer, Roche